WORKSHOP PENDAMPINGAN GURU MENGHADAPI ANAK BERKEBUTUHAN KHUSUS (ANAK INKLUSI) DI SEKOLAH FORMAL - Sundahry Sundahry; Dhini Mufti; Reni Guswita; Ratih Juwita Novalia (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
Workshop on Teacher Assistance in Facing Children with Special Needs (Inclusiv Children) in Formal Schools at UPT SDN 03 Simpang is located at Jl. Ampang Pulai, Kec. Koto XI Canal, Kab. South Coast Prov. West Sumatra aims to explore inclusive education, ABK, and filling out ABK assessments. This workshop presents materials: the concept of inclusive education, types of special needs children, and assessment of special needs children. The method of implementing PKM carried out in this activity is in the form of providing basic theories regarding the concept of inclusive education, ABK, and ABK assessment. Participants are asked to do exercises to understand filling out the ABK assessment that has been described previously. After the demonstration was completed, a question and answer session was held to enrich the socialization materials presented.The training program has been carried out for two days. This activity begins with a survey, preparation, implementation, and report generation. The output targets are: participants (elementary teachers) are able to face ABK and fill out ABK